2015
DOI: 10.1088/0957-4484/26/50/505704
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy identification of Al-sites on ultrathin aluminum oxide film on NiAl(110)

Abstract: Ultrathin alumina film formed by oxidation of NiAl(110) was studied by non-contact atomic force microscopy in an ultra high vacuum at room temperature with the quest to provide the ultimate understanding of structure and bonding of this complicated interface. Using a very stiff Si cantilever with significantly improved resolution, we have obtained images of this system with unprecedented resolution, surpassing all the previous results. In particular, we were able to unambiguously resolve all the differently co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…S1, supplemental material 45 ). This structure without bulk counterpart matches perfectly diffraction 18 , near-field microscopy 31,[46][47][48][49] and spectroscopic data 25,31,33 .…”
Section: Introductionsupporting
confidence: 82%
“…S1, supplemental material 45 ). This structure without bulk counterpart matches perfectly diffraction 18 , near-field microscopy 31,[46][47][48][49] and spectroscopic data 25,31,33 .…”
Section: Introductionsupporting
confidence: 82%
“…AFM is a well-established method for characterizing topography of surfaces; however, it is recommended in previous studies as a combined approach with SEM, to ascertain the quality of homogeneity of the samples on a large scale. Moreover, the uneven distribution of peaks and valleys on the chitosan coating, significantly affected the Ra and Rq values of a film surface [38][39][40]. The Ra and Rq values of composite coatings may also be affected by the addition and interaction of NPs.…”
Section: Afm Analysismentioning
confidence: 99%
“…This might be due the interaction among the water, emulsifier, acetic acid, glycol and the increased chitosan in the system. Moreover, the inhomogeneous distribution of micropores, meaning the uneven distribution of the peaks and valleys in the chitosan coating, could significantly affect the Ra and Rq values of film surface [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The surfaces with fewer micropores could become less sharp and show a smoother appearance, which might also be influenced by the added concentration of chitosan.…”
Section: Resultsmentioning
confidence: 99%
“…The good uniform microstructure of chitosan coating films are observed from SEM images, which indicates that the mixtures of chitosan, acetic acid and glycerol are homogenous in the coating film. These results could be explained by the interaction of the higher amount chitosan with other components in the prepared system, the adsorbed action of surface tension for coating liquid and the different number of micropores formed on the film surface [ 49 , 50 , 51 , 52 ]. Xing et al (2011b) also reported that the roughness value of control group was higher than the chitosan–oil coated group fruits [ 9 ].…”
Section: Resultsmentioning
confidence: 99%